A calcium-based hydrotalcite PVC composite heat stabilizer and preparation method thereof

By using calcium-based hydrotalcite PVC composite thermal stabilizer with specific composition and preparation process, the problem of insufficient thermal stability performance of soft films for decorative ceilings in the prior art is solved, and better thermal stability and initial hue effect are achieved, and it is suitable for a variety of PVC products.

CN119219982BActive Publication Date: 2025-04-29SHANDONG HAOXING ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411338643.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-29
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing calcium-based hydrotalcite PVC composite thermal stabilizer has insufficient thermal stability performance in soft films for decorative ceilings and needs further improvement.

Method used

The calcium-based hydrotalcite PVC composite heat stabilizer consisting of hydrotalcite base material, lubricant, phosphite esters, functional additives, pentaerythritol and antioxidants is used to improve thermal stability and initial chromatic effect through specific preparation processes and raw material ratios.

Benefits of technology

It significantly improves the thermal stability and initial hue of PVC products, ensures product quality and quality, replaces traditional lead salt and organic tin heat stabilizers, and is suitable for a variety of PVC products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059017980000091
    Figure BDA0005059017980000091
Patent Text Reader

Abstract

The invention relates to the technical field of PVC production, in particular to a calcium-based hydrotalcite PVC composite heat stabilizer and a preparation method thereof; the high-altitude light-transmitting projectable ceiling soft film is composed of the following raw materials in parts by weight: 20 to 30 parts of hydrotalcite base material, 3 to 6 parts of lubricant, 3 to 5 parts of phosphite, 10 to 14 parts of functional additive, 4 to 7 parts of pentaerythritol and 2 to 5 parts of antioxidant; the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant are put into a mixing device for mixing and stirring, and after the mixing is completed, the steps of inspection and metering and packaging are carried out in sequence to finally obtain a finished calcium-based hydrotalcite PVC composite heat stabilizer; the calcium-based hydrotalcite PVC composite heat stabilizer prepared by the invention can not only improve the thermal stability of PVC products, but also has an excellent effect of improving the initial hue of PVC products, and effectively guarantees the quality and grade of the PVC products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC production, in particular to a calcium-based hydrotalcite PVC composite heat stabilizer and a preparation method thereof. Background Art

[0002] Polyvinyl chloride plastic has excellent mechanical and electrical properties and low overall cost. It has been widely used in industrial and agricultural production and daily life for many years.

[0003] Hydrotalcite is a layered double metal hydroxide, which is widely used in many fields such as heat stabilizer, catalyst, catalyst carrier, flame retardant, pesticide, sewage treatment agent, electrorheological modifier, medicine, pharmaceutical carrier, etc., and has high economic value.

[0004] In the patent document with application number "CN201510821425.3" and title "A calcium-based hydrotalcite PVC composite heat stabilizer", it is recorded that "the composition of the calcium-based hydrotalcite PVC composite heat stabilizer includes, by mass, 20-60 parts of calcium-based hydrotalcite, 15-55 parts of calcium soap, 5-40 parts of zinc soap, 15-35 parts of lubricant, 1-6 parts of antioxidant, 1-6 parts of light stabilizer, and 4-12 parts of chelating agent. The PVC composite heat stabilizer obtained by the present invention shows better initial coloring inhibition and long-term heat stability performance on PVC than the traditional PVC composite heat stabilizer. The composite heat stabilizer provided by the present invention has good lubrication processability, transparency, weather resistance, and light stability, and has no sulfide pollution. The composite heat stabilizer of the present invention has the characteristics of non-toxicity, environmental protection, low cost, high performance, abundant raw materials, simple manufacturing, etc., is suitable for industrial production, can replace traditional lead salts and expensive organic tin heat stabilizers, and is widely used in PVC pipes, profiles, wires and cables, medical equipment, films and other fields."

[0005] Although the soft film for decorative ceilings manufactured in the above patent documents has the advantages of low cost and weather resistance, its own thermal stabilizer performance is relatively insufficient and still needs further improvement. Based on this, the present invention provides a calcium-based hydrotalcite PVC composite thermal stabilizer and a preparation method thereof to solve the above technical problems. Summary of the invention

[0006] The object of the present invention is to provide a calcium-based hydrotalcite PVC composite heat stabilizer and a preparation method thereof. The prepared calcium-based hydrotalcite PVC composite heat stabilizer can not only improve the thermal stability of PVC products, but also has an excellent effect of improving the initial hue of PVC products, effectively ensuring their quality.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The first aspect of the present invention provides a calcium-based hydrotalcite PVC composite heat stabilizer, which is composed of the following raw materials in parts by weight: 20 to 30 parts of hydrotalcite base material, 3 to 6 parts of lubricant, 3 to 5 parts of phosphite, 10 to 14 parts of functional additives, 4 to 7 parts of pentaerythritol and 2 to 5 parts of antioxidant.

[0009] The present invention is further configured as follows: the preparation process of the hydrotalcite base material is as follows:

[0010] The composite material is added into deionized water at a dosage ratio of 0.15 to 0.25 g / mL, and treated at 120 to 140 r / min for 10 to 14 minutes, and then 0.25 to 0.35% of lanthanum nitrate by weight of the composite material is added thereto, and stirring is continued for 5 to 10 minutes to obtain a first solution;

[0011] The obtained first solution is placed in a water bath at 75-80° C. and 80-100 r / min, the pH is adjusted to 11.2-11.8 with a sodium hydroxide solution, and then kept at 95-100° C. for 12-14 hours to obtain a second solution;

[0012] Add maleic acid in a dosage ratio of 0.06 to 0.12 g / mL into deionized water, and treat at 90 to 120 r / min for 5 to 10 minutes to obtain a third solution;

[0013] Under a nitrogen atmosphere, the second solution and the third solution are mixed, and then refluxed at 100-110° C. for 100-150 min, and then sodium fatty acid methyl ester sulfonate is added thereto, and treated at 100-120 r / min for 50-60 min, and then heat-treated at 150-170° C. for 15-17 h. After cooling and filtering, the mixture is washed with anhydrous ethanol and deionized water for 2-4 times, dried at 70-80° C. for 14-16 h, and ground to obtain a hydrotalcite base material.

[0014] The present invention is further configured as follows: the composite material is formed by mixing calcium nitrate and aluminum nitrate in a mass ratio of 1:0.75-0.85.

[0015] The present invention is further configured as follows: the mixing mass ratio of the second solution to the third solution is 1:0.41-0.52.

[0016] The present invention is further configured as follows: the addition amount of the sodium fatty acid methyl ester sulfonate is 0.4-0.8% of the mass of the second solution.

[0017] The present invention is further configured as follows: the lubricant is selected from any one of paraffin and stearic acid.

[0018] The present invention is further configured as follows: the preparation process of the functional additive is as follows:

[0019] Place oleic acid in ethanol at a mass ratio of 1:12-15, and stir at 80-140 r / min for 10-20 min;

[0020] Then the temperature is raised to 84-88°C, diethylene glycol monobutyl ether with a mass percentage of 82-85% of oleic acid and zinc oxide with a mass percentage of 410-430% of oleic acid are added thereto, stirring is continued for 5-10 minutes, heat treatment is carried out for 150-170 minutes, and drying is carried out at 50-60°C for 20-25 hours to obtain a functional additive.

[0021] The present invention is further configured as follows: the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.

[0022] The second aspect of the present invention: also provides a method for preparing the above-mentioned calcium-based hydrotalcite PVC composite heat stabilizer, comprising the following steps:

[0023] Step 1: accurately weighing a hydrotalcite base material, a lubricant, a phosphite, a functional additive, pentaerythritol and an antioxidant, and putting the hydrotalcite base material, the lubricant, the phosphite, the functional additive, pentaerythritol and the antioxidant into a mixing device for mixing and stirring;

[0024] Step 2: After the mixing is completed, the product is tested, measured and packaged to obtain the finished product of calcium-based hydrotalcite PVC composite heat stabilizer.

[0025] The present invention is further configured as follows: in step 1, the rotation speed of the mixing and stirring is 320 to 420 r / min, and the time is 30 to 40 min.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] In the present invention, hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant are used as raw materials, and the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant are put into a mixing device for mixing and stirring. After the mixing is completed, the calcium-based hydrotalcite PVC composite heat stabilizer finished product is finally obtained by inspection and metering packaging steps. The calcium-based hydrotalcite PVC composite heat stabilizer prepared by the present invention can not only improve the thermal stability of PVC products, but also has an excellent effect of improving the initial hue of PVC products, effectively ensuring its quality. The calcium-based hydrotalcite PVC composite heat stabilizer and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] The present embodiment provides a calcium-based hydrotalcite PVC composite heat stabilizer, which is composed of the following raw materials in parts by weight: 20 parts of hydrotalcite base material, 3 parts of lubricant, 3 parts of phosphite, 10 parts of functional additives, 4 parts of pentaerythritol and 2 parts of antioxidant.

[0031] The preparation process of the hydrotalcite base material is as follows:

[0032] The composite material was put into deionized water at a dosage ratio of 0.15 g / mL, treated at 120 r / min for 10 min, and then 0.25% of lanthanum nitrate by weight of the composite material was added thereto, and stirring was continued for 5 min to obtain a first solution; the obtained first solution was placed in a water bath at 75°C and 80 r / min, the pH was adjusted to 11.2 with sodium hydroxide solution, and then kept at 95°C for 12 h to obtain a second solution; maleic acid was put into deionized water at a dosage ratio of 0.06 g / mL; in water, treated at 90r / min for 5min to obtain a third solution; in a nitrogen atmosphere, the second solution and the third solution were mixed, and then refluxed at 100°C for 100min, and then sodium fatty acid methyl ester sulfonate was added thereto, treated at 100r / min for 50min, and then kept warm at 150°C for 15h. After cooling and filtering, the mixture was washed twice with anhydrous ethanol and deionized water respectively, dried at 70°C for 14h, and ground to obtain a hydrotalcite base material.

[0033] Furthermore, the composite material is prepared by mixing calcium nitrate and aluminum nitrate in a mass ratio of 1:0.75.

[0034] The mixing mass ratio of the second solution to the third solution is 1:0.41.

[0035] In this embodiment, it should be noted that maleic acid was purchased from Shandong Hui'an Chemical Co., Ltd., and sodium fatty acid methyl ester sulfonate was purchased from Jinan Daorong Chemical Co., Ltd.

[0036] The added amount of sodium fatty acid methyl ester sulfonate is 0.4% of the mass of the second solution.

[0037] In addition, paraffin is used as lubricant.

[0038] In this embodiment, it should be noted that paraffin wax was purchased from Chengdu Hengyi Chemical Products Co., Ltd.

[0039] The preparation process of functional additives is as follows:

[0040] Oleic acid is placed in ethanol at a mass ratio of 1:12 and stirred at 80 r / min for 10 minutes; then the temperature is raised to 84°C, and diethylene glycol monobutyl ether (82% by mass of oleic acid) and zinc oxide (410% by mass of oleic acid) are added thereto, and stirring is continued for 5 minutes. The mixture is heat-insulated for 150 minutes and dried at 50°C for 20 hours to obtain a functional additive.

[0041] Among them, antioxidant 1010 is selected as the antioxidant.

[0042] In addition, this embodiment also provides a method for preparing the above calcium-based hydrotalcite PVC composite heat stabilizer, comprising the following steps:

[0043] Step 1: Accurately weigh the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant, and put the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant into a mixing device for mixing and stirring.

[0044] The mixing speed is 320 r / min and the time is 30 min.

[0045] Step 2: After the mixing is completed, the product is tested, measured and packaged to obtain the finished product of calcium-based hydrotalcite PVC composite heat stabilizer.

[0046] Example 2

[0047] The preparation method of the calcium-based hydrotalcite PVC composite heat stabilizer provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the calcium-based hydrotalcite PVC composite heat stabilizer in this embodiment are different; the specific raw material composition and the specific preparation method of the calcium-based hydrotalcite PVC composite heat stabilizer in this embodiment are as follows:

[0048] A calcium-based hydrotalcite PVC composite heat stabilizer is composed of the following raw materials in parts by weight: 25 parts of hydrotalcite base material, 4 parts of lubricant, 4 parts of phosphite, 12 parts of functional additives, 5 parts of pentaerythritol and 4 parts of antioxidant.

[0049] The preparation process of the hydrotalcite base material is as follows:

[0050] The composite material was added into deionized water at a dosage ratio of 0.2 g / mL, and treated at 130 r / min for 10 to 14 min, and then 0.3% of lanthanum nitrate by weight of the composite material was added thereto, and the stirring was continued for 7 min to obtain a first solution; the obtained first solution was placed in a water bath at 77°C and 90 r / min, and the pH was adjusted to 11.5 with sodium hydroxide solution, and then kept at 97°C for 13 h to obtain a second solution; maleic acid was added into the water at a dosage ratio of 0.06 to 0.12 g / mL; In deionized water, treat at 110r / min for 7min to obtain a third solution; under a nitrogen atmosphere, mix the second solution and the third solution, reflux at 105°C for 125min, then add sodium fatty acid methyl ester sulfonate, treat at 110r / min for 55min, and then keep warm at 160°C for 16h. After cooling and filtering, wash with anhydrous ethanol and deionized water for 3 times respectively, dry at 75°C for 15h, and grind to obtain a hydrotalcite base material.

[0051] Furthermore, the composite material is prepared by mixing calcium nitrate and aluminum nitrate in a mass ratio of 1:0.8.

[0052] The mixing mass ratio of the second solution to the third solution is 1:0.46.

[0053] In this embodiment, it should be noted that maleic acid was purchased from Shandong Hui'an Chemical Co., Ltd., and sodium fatty acid methyl ester sulfonate was purchased from Jinan Daorong Chemical Co., Ltd.

[0054] The added amount of sodium fatty acid methyl ester sulfonate is 0.6% of the mass of the second solution.

[0055] In addition, stearic acid is selected as the lubricant.

[0056] In this embodiment, it should be noted that stearic acid was purchased from Wuxi Jingke Chemical Co., Ltd.

[0057] The preparation process of functional additives is as follows:

[0058] Oleic acid was placed in ethanol at a mass ratio of 1:13 and stirred at 120 r / min for 15 min; then the temperature was raised to 86°C, and diethylene glycol monobutyl ether (83% by mass of oleic acid) and zinc oxide (420% by mass of oleic acid) were added thereto. After stirring for 7 min, the mixture was kept warm for 160 min and dried at 55°C for 22 h to obtain a functional additive.

[0059] Among them, antioxidant 1076 is selected as the antioxidant.

[0060] In addition, this embodiment also provides a method for preparing the above calcium-based hydrotalcite PVC composite heat stabilizer, comprising the following steps:

[0061] Step 1: Accurately weigh the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant, and put the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant into a mixing device for mixing and stirring.

[0062] The mixing speed is 370 r / min and the time is 35 min.

[0063] Step 2: After the mixing is completed, the product is tested, measured and packaged to obtain the finished product of calcium-based hydrotalcite PVC composite heat stabilizer.

[0064] Example 3

[0065] The preparation method of the calcium-based hydrotalcite PVC composite heat stabilizer provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the calcium-based hydrotalcite PVC composite heat stabilizer in this embodiment are different; the specific raw material composition and the specific preparation method of the calcium-based hydrotalcite PVC composite heat stabilizer in this embodiment are as follows:

[0066] A calcium-based hydrotalcite PVC composite heat stabilizer is composed of the following raw materials in parts by weight: 30 parts of hydrotalcite base material, 6 parts of lubricant, 5 parts of phosphite, 14 parts of functional additives, 7 parts of pentaerythritol and 5 parts of antioxidant.

[0067] The preparation process of the hydrotalcite base material is as follows:

[0068] The composite material was put into deionized water at a dosage ratio of 0.25 g / mL, treated at 140 r / min for 14 min, and then 0.35% of lanthanum nitrate by weight of the composite material was added thereto, and stirring was continued for 10 min to obtain a first solution; the obtained first solution was placed in a water bath at 80°C and 100 r / min, the pH was adjusted to 11.8 with sodium hydroxide solution, and then kept at 100°C for 14 h to obtain a second solution; maleic acid was put into deionized water at a dosage ratio of 0.12 g / mL; The mixture was stirred for 10 minutes at 120 r / min in water to obtain a third solution. The second solution and the third solution were mixed under a nitrogen atmosphere, and then refluxed at 110°C for 150 minutes. Then, sodium fatty acid methyl ester sulfonate was added thereto, and the mixture was treated at 120 r / min for 60 minutes. The mixture was then heat-treated at 170°C for 17 hours. After cooling and filtering, the mixture was washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 80°C for 16 hours. The hydrotalcite base material was ground.

[0069] Furthermore, the composite material is prepared by mixing calcium nitrate and aluminum nitrate in a mass ratio of 1:0.85.

[0070] The mixing mass ratio of the second solution to the third solution is 1:0.52.

[0071] In this embodiment, it should be noted that maleic acid was purchased from Shandong Hui'an Chemical Co., Ltd., and sodium fatty acid methyl ester sulfonate was purchased from Jinan Daorong Chemical Co., Ltd.

[0072] The added amount of sodium fatty acid methyl ester sulfonate is 0.8% of the mass of the second solution.

[0073] In addition, paraffin is used as lubricant.

[0074] In this embodiment, it should be noted that paraffin wax was purchased from Chengdu Hengyi Chemical Products Co., Ltd.

[0075] The preparation process of functional additives is as follows:

[0076] Oleic acid is placed in ethanol at a mass ratio of 1:15 and stirred at 140r / min for 20 minutes; then the temperature is raised to 88°C, and diethylene glycol monobutyl ether (85% by mass of oleic acid) and zinc oxide (430% by mass of oleic acid) are added thereto. After stirring for 10 minutes, the mixture is kept warm for 170 minutes and dried at 60°C for 25 hours to obtain a functional additive.

[0077] Among them, the antioxidant is antioxidant CA.

[0078] In addition, this embodiment also provides a method for preparing the above calcium-based hydrotalcite PVC composite heat stabilizer, comprising the following steps:

[0079] Step 1: Accurately weigh the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant, and put the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant into a mixing device for mixing and stirring.

[0080] The mixing speed is 420 r / min and the time is 40 min.

[0081] Step 2: After the mixing is completed, the product is tested, measured and packaged to obtain the finished product of calcium-based hydrotalcite PVC composite heat stabilizer.

[0082] Comparative Example 1: The difference from Example 1 is that in this example, an equal amount of hydrotalcite (purchased from Jiangsu Jufeng Chemical Technology Co., Ltd.) is used to replace the hydrotalcite base material.

[0083] Comparative Example 2: The difference from Example 1 is that this example does not contain a functional additive.

[0084] Performance test: The composite heat stabilizer samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the composite heat stabilizers provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:

[0085] 1. Thermal stability test: The test method is: add 50 parts by mass of DOP (di-2-ethylhexyl phthalate) and 5 parts by mass of composite thermal stabilizer to 100 parts by mass of PVC resin, mix on a high-speed mixer for 5 minutes, then mix on a double-roll mill for 6 minutes at 150°C, roll into a sheet sample with a thickness of 1mm on a tablet press, and then cut the sheet sample into a 2cm×2cm test piece. Place the sample in a heat aging test box at 200±1°C for static aging test.

[0086] 2. Color change test: The test method is: according to the thermal stability test method, take out a group of test pieces every 10 minutes to observe the hue change and the time when black decomposition occurs.

[0087] The obtained test data are recorded in Table 1 and Table 2 below:

[0088] Table 1 Thermal stability performance test results of each group

[0089]

[0090]

[0091] Table 2 Color change test results of each group

[0092] Group Time to light yellow (min) Example 1 Group 70 Example 2 Group 70 Example 3 Group 70 Comparison group 1 40 Comparison of 2 groups 60

[0093] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the calcium-based hydrotalcite PVC composite heat stabilizer prepared by the present invention can not only improve the thermal stability of PVC products, but also has an excellent effect of improving the initial hue of PVC products, effectively ensuring its quality. This shows that the calcium-based hydrotalcite PVC composite heat stabilizer and its preparation method provided by the present invention have a broader market prospect and are more suitable for promotion.

[0094] In the present invention, hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant are used as raw materials, and the hydrotalcite base material, lubricant, phosphite, functional additive, pentaerythritol and antioxidant are put into a mixing device for mixing and stirring, and after the mixing is completed, the calcium-based hydrotalcite PVC composite heat stabilizer finished product is finally obtained by successively undergoing inspection and metering and packaging processes. The calcium-based hydrotalcite PVC composite heat stabilizer prepared by the present invention can not only improve the thermal stability of PVC products, but also has an excellent effect of improving the initial hue of PVC products, and effectively guarantees its quality.

[0095] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0096] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A calcium-based hydrotalcite PVC composite heat stabilizer, characterized in that: The invention is composed of the following raw materials in parts by weight: 20 to 30 parts of hydrotalcite base material, 3 to 6 parts of lubricant, 3 to 5 parts of phosphite, 10 to 14 parts of functional additive, 4 to 7 parts of pentaerythritol and 2 to 5 parts of antioxidant; The preparation process of the hydrotalcite base material is as follows: The composite material is added into deionized water at a dosage ratio of 0.15 to 0.25 g / mL, and treated at 120 to 140 r / min for 10 to 14 minutes, and then 0.25 to 0.35% of lanthanum nitrate by weight of the composite material is added thereto, and stirring is continued for 5 to 10 minutes to obtain a first solution; The obtained first solution is placed in a water bath at 75-80° C. and 80-100 r / min, the pH is adjusted to 11.2-11.8 with a sodium hydroxide solution, and then kept at 95-100° C. for 12-14 hours to obtain a second solution; Add maleic acid in a dosage ratio of 0.06 to 0.12 g / mL into deionized water, and treat at 90 to 120 r / min for 5 to 10 minutes to obtain a third solution; Under a nitrogen atmosphere, the second solution and the third solution are mixed, and then refluxed at 100-110° C. for 100-150 min, and then sodium fatty acid methyl ester sulfonate is added thereto, and treated at 100-120 r / min for 50-60 min, and then heat-treated at 150-170° C. for 15-17 h, and after cooling and filtering, washed with anhydrous ethanol and deionized water for 2-4 times, respectively, dried at 70-80° C. for 14-16 h, and ground to obtain a hydrotalcite base material; The preparation process of the functional additive is as follows: Place oleic acid in ethanol at a mass ratio of 1:12-15, and stir at 80-140 r / min for 10-20 min; Then the temperature is raised to 84-88°C, diethylene glycol monobutyl ether with a mass percentage of 82-85% of oleic acid and zinc oxide with a mass percentage of 410-430% of oleic acid are added thereto, stirring is continued for 5-10 minutes, heat treatment is carried out for 150-170 minutes, and drying is carried out at 50-60°C for 20-25 hours to obtain a functional additive.

2. A calcium-based hydrotalcite PVC composite heat stabilizer according to claim 1, characterized in that: The composite material is prepared by mixing calcium nitrate and aluminum nitrate in a mass ratio of 1:0.75-0.

85.

3. A calcium-based hydrotalcite PVC composite heat stabilizer according to claim 1, characterized in that: The mixing mass ratio of the second solution to the third solution is 1:0.41-0.

52.

4. The calcium-based hydrotalcite PVC composite heat stabilizer according to claim 1, characterized in that: The added amount of the sodium fatty acid methyl ester sulfonate is 0.4-0.8% of the mass of the second solution.

5. The calcium-based hydrotalcite PVC composite heat stabilizer according to claim 1, characterized in that: The lubricant is selected from any one of paraffin and stearic acid.

6. The calcium-based hydrotalcite PVC composite heat stabilizer according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.

7. The method for preparing a calcium-based hydrotalcite PVC composite heat stabilizer according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: accurately weighing a hydrotalcite base material, a lubricant, a phosphite, a functional additive, pentaerythritol and an antioxidant, and putting the hydrotalcite base material, the lubricant, the phosphite, the functional additive, pentaerythritol and the antioxidant into a mixing device for mixing and stirring; Step 2: After the mixing is completed, the product is tested, measured and packaged to obtain the finished product of calcium-based hydrotalcite PVC composite heat stabilizer.

8. The method for preparing a calcium-based hydrotalcite PVC composite heat stabilizer according to claim 7, characterized in that: In the step 1, the mixing and stirring is carried out at a rotation speed of 320 to 420 r / min and for a time of 30 to 40 min.

Citation Information

Patent Citations

  • Calcium-based hydrotalcite PVC composite heat stabilizer

    CN105348682A

  • PVC compound thermal stabilizer comprising hydrotalcite with controllable radius-thickness ratio and production method of hydrotalcite with controllable radius-thickness ratio

    CN110183790A